Rethinking Education from Patients' Perspectives - Harrison, Jill; Frampton, Susan; McNeal, Gloria J.; Todorova, Elena; Wahl, Carol; Kreiger, Joan (ABNF Journal, 2019)
Person-centered care (PCC) is a term used to describe an individualized approach to patient care that engages patients and families as partners in meaningful ways to create a comprehensive, collaborative, and customized plan and experience of care. Although some healthcare fields of study, such as the Quality and Safety Education for Nurses (QSEN) model, have adopted and integrated person-centered care concepts and competencies into their curricula, there remains a critical gap in higher education to systematically integrate person-centered care into the curricula and assessment of interprofessional healthcare fields of study. While the delivery of person-centered care by healthcare professionals requires education and training in PCC concepts, this training has primarily occurred on the job, without a standardized and comprehensive curriculum to systematically teach and assess PCC competencies to students in interprofessional healthcare and medical degree programs. Until recently, the educational foundations for healthcare disciplines were drawn primarily from biomedical, business, and nursing models, not from patients' points of view. In this article, we consider why teaching and evaluating PCC concepts should be the foundation of all interprofessional health education. We first review the perspectives of relevance to our argument and then advocate for a person-centered paradigm shift for interprofessional healthcare and medical education and training. Next, we argue that integrating and evaluating students' understanding and application of PCC concepts in all healthcarerelated disciplines will ensure that graduates receive the most current and relevant preparation for careers in healthcare and that this aligns with the expectations of patients as consumers.
Keywords: Curriculum; Education; Evaluation; GenderWatch; Interprofessional education; Patient; Person-centered care; Teaching method; Y; dept.hms; peer-reviewed; ⛔ No DOI found